Полікультурна освіта майбутніх соціальних педагогів: теоретико-методичний аспект - Гуренко, Ольга Іванівна (Ткачук О. В., 2014)
У монографії висвітлено теоретичні й методичні засади полікультурної освіти майбутніх соціальних педагогів. Подано авторську модель полікультурної освіти майбутніх соціальних педагогів та методику її поетапної реалізації в умовах вишу за рахунок застосування аксіологічного, культурологічного, системного, компетентнісного, освітньо-просторового, ситуативного, трансдисциплінарного підходів. Для викладачів вищих педагогічних навчальних закладів, практичних працівників соціально-педагогічної сфери, курсантів інститутів післядипломної педагогічної освіти, магістрантів, студентів.
Multicultural education of future social educators: theoretical and methodological aspect
The monograph highlights the theoretical and methodological principles of multicultural education of future social educators. The author's model of multicultural education of future social educators and the methodology of its phased implementation in the conditions of the university through the use of axiological, cultural, systemic, competence, educational, spatial, situational, transdisciplinary approaches are presented. For teachers of higher pedagogical educational institutions, practical workers of the social and pedagogical sphere, cadets of institutes of postgraduate pedagogical education, undergraduates, students.
Keywords: полікультурна освіта; полікультурна компетентність; multicultural education; multicultural competence